Reclassification of Mongolian Diffuse Gliomas According to the Revised 2016 World Health Organization Central Nervous System Tumor Classification - Enkhee Ochirjav; Bayarmaa Enkhbat; Tuul Baldandorj; Gheeyoung Choe (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background The 2016 World Health Organization (WHO) classification of central nervous system (CNS) tumors has been modified to incorporate the IDH mutation and 1p/19q co-deletion in the diagnosis of diffuse gliomas. In this study, we aimed to evaluate the feasibility and prognostic significance of the revised 2016 WHO classification of CNS tumors in Mongolian patients with diffuse gliomas. Methods A total of 124 cases of diffuse gliomas were collected, and tissue microarray blocks were made. IDH1 mutation was tested using immunohistochemistry, and 1p/19q co-deletion status was examined using fluorescence in situ hybridization analysis. Results According to the 2016 WHO classification, 124 cases of diffuse brain glioma were reclassified as follows: 10 oligodendroglioma, IDHmut and 1p/19q co-deleted; three anaplastic oligodendroglioma, IDHmut and 1p/19q co-deleted; 35 diffuse astrocytoma, IDHmut, 11 diffuse astrocytoma, IDHwt, not otherwise specified (NOS); 22 anaplastic astrocytoma, IDHmut, eight anaplastic astrocytoma, IDHwt, NOS; and 35 glioblastoma, IDHwt, NOS, respectively. The 2016 WHO classification presented better prognostic value for overall survival in patients with grade II tumors than traditional histological classification. Among patients with grade II tumors, those with oligodendroglioma IDHmut and 1p/19q co-deleted and diffuse astrocytoma IDHmut showed significantly higher survival than those with diffuse astrocytoma IDHwt, NOS (p<.01). Conclusions Mongolian diffuse gliomas could be reclassified according to the new 2016 WHO classification. Reclassification revealed substantial changes in diagnosis of both oligodendroglial and astrocytic entities. We have confirmed that the revised 2016 WHO CNS tumor classification has prognostic significance in Mongolian patients with diffuse gliomas, especially those with grade II tumors.